Testing Procedures and Certification of Highly Automated and Autonomous Road Vehicles - Shadrin, S. S.; Ivanov, A. M. (2021 Systems of Signals Generating and Processing in the Field of on Board Communications, 2021)
This article is dedicated to the analysis of existing regulatory and legal acts in the field of regulating the use and testing of highly automated and autonomous vehicles in the EU, USA, and Russia. The statistical information of road accidents relevant for the Russian conditions is presented for the purpose of localizing the critical test scenarios. The results of virtual tests of pedestrian protection system (PPS) conducted in Siemens Prescan software for different weather and lighting conditions are presented, as well as some other practical cases of advanced driver assistance systems (ADAS) simulation.